2012 Kansas Performance Tests with Cotton Varieties - Haag, Lucas A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
This publication presents the results of performance tests with cotton varieties. Descriptive information is presented with the results for each test. This information, including soil type, establishment methods, fertilization, pest control, irrigation, harvest dates, and growing conditions unique to that location, can help explain test and/or variety performance.
Keywords: Lint yield; Yield as a percentage of test average; Cotton fiber quality; Kansas; Cotton varieties